Initial Therapy of Bacterial Meningitis with Cefuroxime: Experience in 167 Children - Lissette Navas; Susan M King; Ronald Gold (Canadian Journal of Infectious Diseases)
The morbidity and mortality of patients with bacterial meningitis treated initially with cefuroxime were studied and compared with the results of a previous prospective study of patients treated initially with ampicillin plus chloramphenicol in the same institution from 1979 to 1983. A retrospective chart review was completed in all cases of microbiologically confirmed bacterial meningitis admitted to the Hospital for Sick Children in Toronto, Ontario between January 1, 1984 and August 1, 1988. During this period all patients were treated initially with intravenous cefuroxime. The 167 children reviewed ranged in age from six weeks to 17.1 years (median 11.6 months). The case fatality rate was 7.8% and the rate of hearing deficit 13%. There were no statistically significant differences in abnormal neurological outcome (20 versus 20%, respectively), hearing loss (12.9 versus 13%, respectively), and case fatality rate (6.4 versus 7.8%, respectively) between the cohort of 1979–83 and the present study. The rate of hearing loss following meningitis caused by Haemophilus influenzae type b increased from 7.3 to 11.7% (P=0.26).